PENGARUH KUALITAS PELAYANAN, FASILITAS DAN LOKASI TERHADAP KEPUTUSAN MENGINAP DI FAVEHOTEL SUNSET SEMINYAK BADUNG - Ni Kadek Mayuni (STIE BIITM, 2019)
The analysis technique used is Multiple Regression, Determination, T Test and F Test with an error rate of 5%. From the results of the using the SPSS program, then the following results are obtained: There is a positive and significant partial effect of the facility on the decision to stay, while Service Quality has a positive but not significant influence on the decision to stay and Location has no significant influence on the decision to stay, preferably the hotel management needs to pay attention to the location that is easily accessible so that it is easier for consumers to go to their destination. Besides that there is a simultaneous and significant positive effect if service quality (X1) facilities (X2) and location (X3) on Stay Decision (Y) at favehotel Sunset Seminyak giving contribution / influence of 15.3% and 87.4% again determined by other factors not discussed in this study, while the regression equation is Y = 4,648 + 0,184X1 + 0,235X2 + 0,093X3. From the results of these studies it can be concluded that there is an influence of service quality, facilities and location on the decision to stay at favehotel Sunset Seminyak, management should do marketing simultaneously / together because it will be more instrumental and follow up on complaints from customers.